Multilevel risk analysis of postoperative pulmonary complications following mandibular fractures: a retrospective cohort study based on patient characteristics and healthcare system factors - Shuwei Liao; Guanxiong Zhu; Liting Zeng; Yang Yu; Zeyu Zhang; Hongru Zhang; Jingyuan Wang; Lina Yu (BMC Oral Health)
Abstract Background Pulmonary complications (PPCs) following mandibular fractures are serious post—surgery problems. This study analyzed risk factors of PPCs following mandibular fractures using the National Inpatient Sample (NIS) database, aiming to help clinicians specify surgical protocols and postoperative care for patients. Method A retrospective cohort study was conducted to examine patient demographics, hospital characteristics and preoperative comorbidities for identifying risk factors associated with postoperative pulmonary complications (PPCs). The analysis utilized data from the National Inpatient Sample (NIS) database containing patients undergoing mandibular surgery between 2010 and 2019. The cohort was stratified into two groups: those with PPCs and non-PPC cases. Statistical associations were evaluated through univariate and multivariate logistic regression analyses. A threshold of P ≤ 0.001 was set for statistical significance. Results The study included 41,984 adult patients (33,017 male; 8,967 female; aged ≥ 18 years), with 3,514 cases of postoperative pulmonary complications (PPCs) subclassified as: 1,347 pneumonia, 2,452 acute respiratory failure (ARF), and 212 pulmonary embolism (PE). For patients with PPCs, there was a significant increase in the age by 8 years, length of stay (LOS) by 12 days, the total charge (TOTCHG) by $163,579, and the mortality rate by 8.9%. Following the analysis, the following risk factors and their incidence were identified: number of comorbidities ≥ 3 (OR = 3.72, 40.4%), fluid and electrolyte disorders (OR = 2.66, 46.7%), obesity (OR = 1.38, 5.0%), congestive heart failure (OR = 1.24, 4.4%), coagulopathy (OR = 1.94, 12.4%), peripheral vascular disorders (OR = 1.53, 5.7%), pulmonary circulation disorders (OR = 7 .93, 4.1%), respiratory diseases (OR = 3.93, 5.2%), other neurological disorders (OR = 1.57, 15.2%), and paralysis (OR = 2.43, 5.0%). Conclusion In this study, statistical methods were employed to identify the risk factors for pulmonary complications following mandibular fractures, which can aid in the establishment of a sound surgical procedure and postoperative care.